Removal of Arsenic from Water Using Natural Manganese Ore Globules - Thi Hai, Nguyen; Hoai, Ta Thi; Tuan, Nguyen Quoc; Hong, Nguyen Thi; Ha, Nguyen Thi Hoang (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 3DO - 10.25073/2588-1094/vnuees.5153, 2025)
This study investigated the removal capacity of arsenic (As) by natural manganese ore materials (OMN). We used scanning electron microscopy (SEM), X-Ray Fluorescence (XRF), and point-of-zero charge pH PZC   to characterize the OMN. The As adsorption capacity of OMN was tested at different pHs and flow rates in the adsorption columns. The results indicated that pH affected the As removal capacity of OMN. The column adsorption was carried out continuously at a constant flow rate of 10 mL/min for 30 days. The feed solutions with As concentrations of 0.3 and 0.1 mg/L were pumped into two columns in an up-flow mode. Two column adsorptions were 7.5 cm in diameter and 17.5 cm in height and were packed with 900 g of OM. During the 30 days of the experiments, As concentrations in the effluent ranged from 0.006-0.217 mg/L and 0.003-0.051 mg/L, respectively, when As concentrations in the influent were 0.3 and 0.1 mg/L. The As concentration in the treated solution during the first 12 days, when using a solution containing As at a concentration of 0.1 mg/L, was below the WHO guidelines for drinking water quality and national technical regulation on domestic water quality (QCVN 01-1:2018/BYT) (0.01 mg/L for As).